Pharmacological Studies in Phytotherapy of Acne and Infectious Skin Diseases: a Systematic Review - S Kianbakht (Institue of Medicinal Plants, ACECR, 2013)
The use of medicinal plants for the treatment of acne and other infectious skin diseases is very common. Here, pharmacological studies on the medicinal plants which may be effective in the treatment of acne and infective skin diseases published in the databases PubMed and Scopus from the beginning of the year 1980 to the end of April of the year 2013 have been searched and discussed. Keywords including medicinal plants, herbs, botanicals, phytomedicine, phytotherapy, herbal therapy and herbal medicine with dermatology, skin, acne vulgaris, antibacterial, antiviral, antifungal and antimicrobial were entered in the databases. Totally 56 articles concerning clinical and nonclinical studies were found. Afterward, the quality of each study was determined. Examples of such plants include Vitex agnus-castus, Ocimum gratissimum, Aloe vera, Solanum dulcamara, Commiphora mukul, Mahonia aquifolium, Melaleuca alternifolia, species of the genus Eucalyptus, Camellia sinensis and Allium sativum. Medicinal plants can have an important role in the treatment of acne and other infectious skin diseases. However, scant studies have been conducted in this field so far and more studies especially on the efficacy and safety of the plants' clinical use in humans are needed.